Sodium Acetate Inhibit TGF-β1-Induced Activation of Hepatic Stellate Cells by Restoring AMPK or c-Jun Signaling - Li, Weiwei; Deng, Mingjuan; Gong, Jiahui; Zhang, Xiaoying; Ge, Shaoyang; Zhao, Liang (Frontiers in Nutrition, 2021)
Short-chain fatty acids (SCFAs) are crucial gut microbial metabolites that play a major role in the occurrence and development of hepatic fibrosis (HF). However, the effect of SCFAs on hepatic stellate cells (HSCs), the major pro-fibrogenic cells, is yet undefined. In this study, the effects of three major SCFAs (acetate, propionate, and butyrate) were assessed on the activation of HSCs. LX2 cells were activated with TGF-β1 and treated with sodium acetate (NaA), sodium propionate (NaP), or sodium butyrate (NaB). SCFA treatment significantly reduced the protein levels of α-SMA and the phosphorylation of Smad2 and decreased the mRNA expression of Acta2/Colla1/Fn in cells compared to the TGF-β1 treatment. Among the three SCFAs, NaA revealed the best efficacy at alleviating TGF-β1-induced LX2 cell activation. Additionally, acetate accumulated in the cells, and G protein-coupled receptor 43 (GPR43) silencing did not have any impact on the inhibition of LX2 cell activation by NaA. These findings indicated that NaA enters into the cells to inhibit LX2 cell activation independent of GPR43. The results of phosphokinase array kit and Western blot indicated that NaA increased the AMP-activated protein kinase (AMPK) activation and reduced the phosphorylation of c-Jun in cultured LX2 cells, and siRNA-peroxisome proliferator-activated receptor-gamma (PPARγ) abolished the inhibitory effects of NaA against TGF-β1-induced LX2 cell activation. In conclusion, this study showed that NaA inhibited LX2 cell activation by activating the AMPK/PPARγ and blocking the c-Jun signaling pathways. Thus, SCFAs might represent a novel and viable approach for alleviating HF.